2022
DOI: 10.1097/mpg.0000000000003472
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Foreign Body Ingestion Trends in Children: A Comparison of the Pre-Pandemic Period to 2020

Abstract: Foreign body ingestion (FBI) among children is associated with morbidity and mortality. We used the National Electronic Injury Surveillance System to compare FBI trends from 2017-2019 to 2020 during the spread of SARS-CoV-2. The pandemic and associated stay-at-home orders were associated with uptrends in button battery and magnet ingestions but unchanged total FBI trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
2
1
2
Order By: Relevance
“…The association between the COVID-19 pandemic and increasing trends in pediatric foreign body ingestion has been witnessed nationally and internationally. Before the pandemic, the main age of foreign body occurrence was toddler (58.64%), and the main age of foreign body occurrence during the pandemic was also toddler (53.78%), which is consistent with the results reported by multiple clinical studies (18)(19)(20). No matter before or during the pandemic, for children aged 1-18 years, with the increase of age and the improvement of safety awareness, the number of foreign bodies is significantly reduced.…”
Section: Discussionsupporting
confidence: 88%
“…The association between the COVID-19 pandemic and increasing trends in pediatric foreign body ingestion has been witnessed nationally and internationally. Before the pandemic, the main age of foreign body occurrence was toddler (58.64%), and the main age of foreign body occurrence during the pandemic was also toddler (53.78%), which is consistent with the results reported by multiple clinical studies (18)(19)(20). No matter before or during the pandemic, for children aged 1-18 years, with the increase of age and the improvement of safety awareness, the number of foreign bodies is significantly reduced.…”
Section: Discussionsupporting
confidence: 88%
“…While access to magnets and rate of magnet ingestions have ebbed and flowed in response to regulatory action, morbidity, and mortality of button battery ingestions in the United States has steadily climbed (11,12) with limited regulations. Similar to the impact of the pandemic on magnet ingestions reported by Shaul et al (6), Geibel et al (13), in the current issue also report a concerning increase in magnet and button battery ingestions during this period. In addition, the authors found a statistically significant increase in foreign body ingestions in patients between 6 and 10 years of age during the COVID pandemic, one of the age groups most impacted by stay at home orders, compared to pre-pandemic rates, and an increase of ingestions occurring at home compared to school.…”
supporting
confidence: 84%
“…Some authors observed a rise in button battery ingestions [9,12,16,18]; however, that was not observed in our institution. Our study found [9,16] an increasing presence of magnetic objects in children in this period (p = 0.0038).…”
Section: Discussioncontrasting
confidence: 58%
“…Some authors observed a rise in button battery ingestions [9,12,16,18]; however, that was not observed in our institution. Our study found [9,16] an increasing presence of magnetic objects in children in this period (p = 0.0038). Especially for magnetic balls, there is higher risk of perforation and need for a much more serious intervention [19].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation